Probing into digitalisation's influence on internal customer satisfaction: An angle from internal customers of shared service organisations - NAIDU, Prashalini; JAIS, Juraifa; RENGANATHAN, Tamil Selvi; Khudari, Mohamed (Edelweiss Applied Science and Technology, 2025)
This paper aims to investigate the impact of the pandemic on shared services and the influence of digitalization on internal customer satisfaction in shared service organizations. Using a qualitative approach, this paper provides details of interviews conducted with internal customers from several organizations. The findings reveal that COVID-19 impacts shared services and that digitalization is positively related to internal customer satisfaction in shared service centers. One limitation of the study is that it only included interviews with six internal customers, highlighting the need for a wider population to be targeted in future studies. Future studies may instead consist of focus groups or interviews with shared service providers. The outcome of this study will benefit organizations attempting to implement shared services to recognize beforehand the significance of having adequate digital facilities in improving business processes so that customer satisfaction can be achieved. Although digitalization has been researched and proven to be a significant catalyst towards achieving customer satisfaction in industries such as education, banking, and airlines, there is limited evidence and studies of the same in the shared service industry.